2008
DOI: 10.1016/j.trstmh.2008.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni morbidity among adults in two villages along Lake Victoria shores in Mwanza District, Tanzania

Abstract: The study aimed to describe morbidity patterns due to intestinal schistosomiasis in adults living in two villages along the southern shores of Lake Victoria, Mwanza District, Tanzania. Nine hundred and fifty persons from Msozi and 497 from Sangabuye, aged between 14 and 87 years, were examined by abdominal ultrasound according to the Niamey protocol. Liver image patterns (LIP) A and B were considered normal and C-F as distinct periportal fibrosis (PPF). The frequency of PPF was higher in Msozi (41.5%) than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
74
7
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(99 citation statements)
references
References 21 publications
17
74
7
1
Order By: Relevance
“…For this reason, most studies of liver pathology consider only patterns of C and higher as schistosomiasis-associated morbidity. 18,[45][46][47] Nevertheless the high prevalence of liver texture pattern B found in our study sample warrants further investigation into its etiology and clinical significance. Liver texture patterns, PBT, and PVD do not fit our criteria as good indicators of morbidity in children because they were not associated with schistosomiasis in this age group.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…For this reason, most studies of liver pathology consider only patterns of C and higher as schistosomiasis-associated morbidity. 18,[45][46][47] Nevertheless the high prevalence of liver texture pattern B found in our study sample warrants further investigation into its etiology and clinical significance. Liver texture patterns, PBT, and PVD do not fit our criteria as good indicators of morbidity in children because they were not associated with schistosomiasis in this age group.…”
Section: Discussionmentioning
confidence: 58%
“…Liver texture patterns, PBT, and PVD do not fit our criteria as good indicators of morbidity in children because they were not associated with schistosomiasis in this age group. This does not appear to be a flaw in the tool (ultrasound examination), but rather reflects the point that these morbidity indicators are typically associated with S. mansoni infection in adults who have more chronic infections 47,48 and are rare in school-aged children. 18,45,49 This suggests that the Niamey protocol, which was designed for assessing morbidity in adult populations, is not adequate for assessing morbidity in children and that development of more age-appropriate tools should be considered.…”
Section: Discussionmentioning
confidence: 94%
“…32 As has been observed in other S. mansoni-endemic countries, the prevalence of fibrosis was shown to increase with increasing age. 20,[32][33][34] We also observed in our study population that adults were more likely to present with portal fibrosis on ultrasound than children. Although this is sometimes reported in children, severe forms of the disease are rarely observed in younger populations.…”
Section: Discussionmentioning
confidence: 51%
“…This finding contrasts with some studies that have that the intensity of infection correlates with disease severity. 20,23,[32][33][34] The lack of association observed in our study could be explained by other possible factors, including the observed high prevalence of S. mansoni infection in this study population, suggesting that the studied participants have repeated exposure.…”
Section: Discussionmentioning
confidence: 97%
“…Malenganisho et al (2008), avaliando duas áreas com níveis de endemicidade distintos na Tanzânia, referiram resultados semelhantes aos nossos. Encontraram espessamento periportal em 41,5% dos indivíduos da área de alta endemicidade e em 16,7% da área de menor endemicidade, concluindo que a frequência da fibrose periportal está associada à prevalência e à intensidade da infecção.…”
Section: Associações Estastisticasunclassified